2020
DOI: 10.1002/jmri.27176
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast Radiomics Approach for Predicting Grades of Nonfunctional Pancreatic Neuroendocrine Tumors

Abstract: Background Endoscopic ultrasound‐guided fine‐needle aspiration is associated with the accurate determination of tumor grade. However, because it is an invasive procedure there is a need to explore alternative noninvasive procedures. Purpose To develop and validate a noncontrast radiomics model for the preoperative prediction of nonfunctional pancreatic neuroendocrine tumor (NF‐pNET) grade (G). Study Type Retrospective, single‐center study. Subjects Patients with pathologically confirmed PNETs (139) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…They demonstrated that the combined model was extremely promising to differentiate PNET G1 from G2/G3 with AUC 0.97 in training and 0.90 in validation cohort. In addition, Bian and colleagues [ 73 ] performed a radiomic model to evaluate preoperative tumor grading in patients affected by non-functional PNETs on 3T MRI and confirmed promising radiomic results. They visually evaluated non-functional PNETs for radiological findings used for the clinical score and then selected a volume of interest (VOI) of the lesion to extract radiomic features.…”
Section: Neuroendocrine Tumorsmentioning
confidence: 86%
“…They demonstrated that the combined model was extremely promising to differentiate PNET G1 from G2/G3 with AUC 0.97 in training and 0.90 in validation cohort. In addition, Bian and colleagues [ 73 ] performed a radiomic model to evaluate preoperative tumor grading in patients affected by non-functional PNETs on 3T MRI and confirmed promising radiomic results. They visually evaluated non-functional PNETs for radiological findings used for the clinical score and then selected a volume of interest (VOI) of the lesion to extract radiomic features.…”
Section: Neuroendocrine Tumorsmentioning
confidence: 86%
“…Therefore, we hypothesized that the tumor biology and heterogeneity were better represented by high-order features. Previous studies recognized the value of assessing pathological features among radiomic features, such as in nonfunctional pancreatic neuroendocrine tumors, soft-tissue masses, and rectal cancer [36][37][38]. However, it remains challenging to associate a single radiomic feature with the complex biological processes of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Bian et al . assessed the radiomic features of non‐contrast MRI images from 139 PNET patients for differentiation between G1 and G2/3 tumors, 34 and a model that combined the radiomic signature and 14 imaging features achieved an AUC of 0.729 in the validation set.…”
Section: Pancreatic Diseasesmentioning
confidence: 99%